Static analysis of a balanced armature receiver. Issue 4 (5th September 2018) - Ziolkowski, Marcin; Kwiatkowski, Wojciech; Gratkowski, Stanislaw; Ziolkowski, Marek
Abstract : Purpose: A balanced armature receiver (BAR) as a special type of electromagnetic acoustic transducers plays a significant role in reproduction of music and speech, active noise control in modern hearing aid and in contemporary in-ear monitors. This paper aims to present a static analysis of the balanced armature receiver based on the lumped network approach (LNA) and the finite element method (FEM). Design/methodology/approach: In this paper, the LNA and two-dimensional FEM are applied to model deflections of the BAR's armature from the equilibrium position. Results of calculations are compared with measurements. Findings: The derived analytical formulas and developed procedure allow for calculation of the armature deflection. Originality/value: Comparing to the previous papers, the reluctance's nonlinearity of the armature has been considered.